2023
DOI: 10.21203/rs.3.rs-3454977/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expansion of endogenous T cells in CSF of pediatric CNS tumor patients undergoing locoregional delivery of IL13R⍺2-targeting CAR T cells: an interim analysis

Leo Wang,
Angela Taravella Oill,
M. Blanchard
et al.

Abstract: Outcomes for pediatric brain tumor patients remain poor, and there is optimism that chimeric antigen receptor (CAR) T cell therapy can improve prognosis. Here, we present interim results from the first six pediatric patients treated on an ongoing phase I clinical trial (NCT04510051) of IL13BBζ-CAR T cells delivered weekly into the lateral cerebral ventricles, identifying clonal expansion of endogenous CAR-negative CD8+ T cells in the cerebrospinal fluid (CSF) over time. Additionally, of the five patients evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…After the administration of the CAR-T in patients with glioblastoma, an increase of T reg cells in the tumor microenvironment was observed, which was associated with a lack of treatment response. In another study, children receiving an IL13 CAR-T intracranially showed no reduction in T reg cells in their cerebrospinal fluid [ 68 ] . Other soluble drivers may originate from metabolic pathways.…”
Section: Biology and Characterization Of T Reg Cellsmentioning
confidence: 99%
“…After the administration of the CAR-T in patients with glioblastoma, an increase of T reg cells in the tumor microenvironment was observed, which was associated with a lack of treatment response. In another study, children receiving an IL13 CAR-T intracranially showed no reduction in T reg cells in their cerebrospinal fluid [ 68 ] . Other soluble drivers may originate from metabolic pathways.…”
Section: Biology and Characterization Of T Reg Cellsmentioning
confidence: 99%